Circulating C19MC MicroRNAs in Preeclampsia, Gestational Hypertension, and Fetal Growth Restriction - Hromadnikova, Ilona; Kotlabova, Katerina; Ondrackova, Marketa; Kestlerova, Andrea; Novotna, Veronika; Hympanova, Lucie; Doucha, Jindrich; Krofta, Ladislav (Mediators of Inflammation, 2013)
The objective of the study was to identify the profile of circulating C19MC microRNAs (miR-516-5p, miR-517*, miR-518b, miR-520a*, miR-520h, miR-525, and miR-526a) in patients with established preeclampsia (n=63), fetal growth restriction (n=27), and gestational hypertension (n=23). We examined the correlation between plasmatic concentrations and expression levels of microRNAs and the severity of the disease with respect to clinical signs, requirements for the delivery, and Doppler ultrasound parameters. Using absolute and relative quantification approaches, increased extracellular C19MC microRNA levels (miR-516-5p, P=0.037, P=0.009; miR-517*, P=0.033, P=0.043; miR-520a*, P=0.001, P=0.009; miR-525, P=0.026, P=0.01; miR-526a, P=0.03, P=0.035) were detected in patients with preeclampsia. The association analysis pointed to no relationship between C19MC microRNA plasmatic concentrations and expression profile and identified risk factors for a poorer perinatal outcome. However, the dependence between the levels of plasmatic C19MC microRNAs and the pulsatility index in the middle cerebral artery and the values of cerebroplacental ratio was demonstrated. The study brought the interesting finding that the upregulation of miR-516-5p, miR-517*, miR-520a*, miR-525, and miR-526a is a characteristic phenomenon of established preeclampsia.